nalyzing the effectiveness of Water Conservation Fee amidst growing water scarcity in India - Khorakiwala, Zainab (Advances in Social Sciences Research Journal, 2019)
Water scarcity has become a significant issue in India, causing the central government to take various measures in addressing the issue through conservation efforts. This includes revising existing and formulating new regulation guidelines, creating awareness about conservation methods, and identifying critical and over-critical areas. In 2018, the concerned ministry endorsed the suggestion to levy Water Conservation Fee (WCF) on industrial, commercial, domestic and agricultural users of water in a bid to conserve depleting groundwater resources. The following paper aims to analyze the effectiveness of WCF, highlighting two major impediments to its success.